Essays on debt renegotiation: determinants, market reaction and earnings management - Eça, João Paulo Augusto (2023)
Companies form contracts with different types of agents. Employees, suppliers, customers, and creditors are examples of agents who establish contractual relationships within a company. These contracts are considered incomplete since it is impossible to specify all the important contingencies that may arise ex-post. Therefore, agents can incorporate contractual mechanisms that allow them to renegotiate the terms of trade in the future, making the renegotiation assume a relevant role in the firms. Specifically concerning debt renegotiation, recent studies have shown important results in the United States and European contexts. Nevertheless, we know little about debt renegotiations in different contexts, such as those found in emerging economies. Thus, I aim to examine debt renegotiations in the Brazilian context, starting from a holistic approach, analyzing debt renegotiation from three different perspectives: i) the creditor\'s perspective (what are the determinants of renegotiation?); ii) the market perspective (how does the market react to the occurrence of renegotiation?); and iii) manager\'s perspective (do managers manage income in order to be successful in renegotiations? The sample selected for this study comprises all non-financial companies listed on the Brazilian stock exchange (B3). The period of the analysis is from 2010 to 2021. Data on renegotiation are unprecedented, collected manually from the analysis of more than three thousand of notes to financial statements. The study of creditors perspective showed that the change in the financial condition of companies (for example, profitability, leverage, size) increases the probability of debt renegotiation for Brazilian companies. Moreover, the results showed that a loss in the firm\'s ability to pay increases the probability of renegotiation having a compensation. The study of the market perspective showed that the capital market reacts positively to the announcement of firms\' renegotiation. However, this reaction tends to be less intense than those presented in other contexts, such as European and U.S. Finally, the study of managers perspective indicated the occurrence of earnings management in the quarters that precede the renegotiation. However, earnings management occurs to reduce accounting profits. More specifically, the study showed that companies in financial difficulty seek to show their bad financial situation in order to obtain better renegotiation terms (for example, covenant softening). Therefore, the three essays offered a key overview of renegotiations in the Brazilian context, thus contributing to a better understanding of renegotiations in emerging economies and improving decision-making by companies and creditors.